Electromagnetic Field Evolution in Relativistic Heavy Ion Collision and Its Effect on Flow of Particles - Gezhagn, Tewodros; Chaubey, A. K. (Frontiers in Physics, 2022)
We compute the electromagnetic fields generated in relativistic heavy-ion collisions using the iEBE-VISHNU framework. We calculated the incremental drift velocity from the four possible sources of electric force (coulomb, Lorentz, Faraday, and plasma-based) on the particles created. The effect of this external electromagnetic field on the flow harmonics of particles was investigated, and we found out that the flow harmonics values get suppressed and rouse in a non-uniform fashion throughout the evolution. More precisely, a maximum of close to 3% increase in elliptic flow was observed. We also found mass as the more dominant factor than charges for the change in flow harmonics due to the created electromagnetic field. On top of that, the magnetic field perpendicular to the reaction plane is found to be sizable, while the different radial electric forces were found to cancel out each other. Finally, we found out that the inclusion of electromagnetic field affects the flow of particles by suppressing or raising it in a non-uniform fashion throughout the evolution.